The Application of Metaphysical Principles to the Empirical World. A Brief Reconstruction of the Core of Kant’s Doctrine of Right - Wyrębska-Đermanović, Ewa (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The rediscovery of Kant’s Doctrine of Right resulted in many attempts to apply Kant’s position to current affairs. This research often faces the problem of defining clear borders of what in Kant’s texts needs to be considered as rational core of his theory and what is merely a theoretically less significant consequence of particular political situation of 18th century. My claim is that in order to be able to adequately apply Kant’s ideas and concepts to the 21st century problems, the process of application of his rational principles to the world of experience must be reconstructed. This will not only bring about the core structure of right but may also determine which elements of Kant’s legal theory are contingent to changing empirical data. I recognise two levels of Kant’s application of the rational principles to human condition, which consecutively determine the rational core of right and secondary structural divisions that emerge from contingent data about political history of mankind. The aim of the article is to investigate the fundamental steps of Kant’s application on the first level, in order to reconstruct the rational core of his legal theory. In the first step I analyse the universal principle of right in order to clarify Kant’s concept of a right. Further, I investigate the axiom of external freedom, which, in conjunction with human condition generates the necessity of using external objects of choice and therefore grounds the emergence of acquired rights. Nevertheless, these rights, as particular legal titles that limit the freedom of others, cannot be reconciled with universal freedom in the state of nature. Therefore, from the establishment of innate and acquired right, there arises the necessity of public right and entering the civil condition.